Integration of network pharmacology and intestinal flora to investigate the mechanism of action of Chinese herbal Cichorium intybus formula in attenuating adenine and ethambutol hydrochloride-induced hyperuricemic nephropathy in rats - Na Li; Mukaram Amatjan; Pengke He; Boheng Zhang; Xianyan Mai; Qianle Jiang; Haochen Xie; Xiaoni Shao (Taylor & Francis Group, 2022)
Context Cichorium intybus L. (Asteraceae) formula (CF) has been applied as a folk medicine to treat hyperuricemic nephropathy (HN). However, the exact mechanism remains unclear.Objective To explore the therapeutic effect and mechanism of CF on HN.Materials and methods Through network pharmacological methods, the targets of the active component of CF against HN were obtained. Subsequently, Male Wistar rats were divided into control, HN, allopurinol (50 mg/kg), CF high-dose (8.64 g/kg) and CF low-dose (2.16 g/kg) groups. The HN model was induced via intragastric administration of adenine (100 mg/kg) and ethambutol hydrochloride (250 mg/kg) for 3 weeks. After CF treatment, biochemical indicators including UA, UREA and CREA were measured. Then, HE staining, qRT-PCR and gut microbiota analysis were conducted to further explore the mechanism.Results The network pharmacology identified 83 key targets, 6 core genes and 200 signalling pathways involved in the treatment of HN. Compared to the HN group, CF (8.64 g/kg) significantly reduced the levels of UA, UREA and CREA (from 2.4 to 1.57 μMol/L, from 15.87 to 11.05 mMol/L and from 64.83 to 54.83 μMol/L, respectively), and mitigated renal damage. Furthermore, CF inhibited the expression of IL-6, TP53, TNF and JUN. It also altered the composition of gut microbiota, and ameliorated HN by increasing the relative abundance of some probiotics.Conclusions This work elucidated the therapeutic effect and underlying mechanism by which CF protects against HN from the view of the biodiversity of the intestinal flora, thus providing a scientific basis for the usage of CF.